2014
DOI: 10.3390/rel5030684
|View full text |Cite
|
Sign up to set email alerts
|

Possible Selves, Body Schemas, and Sādhana: Using Cognitive Science and Neuroscience in the Study of Medieval Vaiṣṇava Sahajiyā Hindu Tantric Texts

Abstract: Abstract:In recent decades, historians of religions have turned to, and developed, entirely new methodologies for the study of religion and human consciousness. Foremost among these are a collection of approaches often termed the "cognitive science of religion" (CSR), typically drawing on cognitive science, neuroscience, linguistics, and contemporary metaphor theory. Although we are still "early" in this enterprise, I hope to show how a meaningful dialogue between religious studies and contemporary neuroscienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…However, the same teacher acknowledged that "as we sit down to sit down to meditate, all this dirt and this refuse that we've lodged into our body and mind matrix is going to break lose; it is going to come up." As Glen Hayes (2014) has pointed out, it is useful to understand subtle body practices as methods of cultivating a novel sense of body schema (Hayes 2014). Practitioners might initially understand the subtle body only conceptually as a novel body image.…”
Section: Some Teachers' Perspectives On Somatic and Affective Purificmentioning
confidence: 99%
“…However, the same teacher acknowledged that "as we sit down to sit down to meditate, all this dirt and this refuse that we've lodged into our body and mind matrix is going to break lose; it is going to come up." As Glen Hayes (2014) has pointed out, it is useful to understand subtle body practices as methods of cultivating a novel sense of body schema (Hayes 2014). Practitioners might initially understand the subtle body only conceptually as a novel body image.…”
Section: Some Teachers' Perspectives On Somatic and Affective Purificmentioning
confidence: 99%
“…In developing this new field at the intersection between contemplative practices and cognitive science, the first challenge is the need for a new vocabulary, as suggested by Hayes (2014). However, it can be difficult to negotiate the boundary between the liberating and transforming experiences found in tantric and yogic practices on one hand and the reductive and embodied domains of cognitive science.…”
Section: Essays In This Special Issuementioning
confidence: 99%
“…ha yoga using cognitive science in a useful essay (Goldberg 2005). Finally, the co-editors of this special issue, Glen Hayes (2003Hayes ( , 2005Hayes ( , 2006Hayes ( , 2012cHayes ( , 2014 and Sthaneshwar Timalsina (2007Timalsina ( , 2012Timalsina ( , 2013Timalsina ( , 2015aTimalsina ( , 2015bTimalsina ( , 2016, have also published numerous works in recent years dealing with various aspects of CSR in the study of Tantra and Yoga.…”
mentioning
confidence: 99%
“…Of particular relevance for this argument, one should pay special attention to Hayes' discussion of what might be going on with the transformation of mind, brain, and body via modification of the prenoetic body schema (the triggering of mirror neurons and relevant neural networks associated with visual, tactile, olfactory, and emotional centers) ( [4], p. 689). Hayes combines this with insights from neuroscientist Patrick McNamara and others to show that there are important overlaps between a human's self-consciousness and sense of self and religious experience.…”
Section: A New "New Vocabulary": Exploring Cognition Neurosciencesmentioning
confidence: 99%
“…Glen Hayes [4] recently suggested that scholars of religions in general, the cognitive science of religion (CSR), metaphor and conceptual blend theorists (broadly construed), and the disciplines collectively known as neurosciences need to develop a "new vocabulary" to express what we are learning and researching regarding contemplative and esoteric traditions ( [4], p. 688). On the one hand, it is likely that collectively we do not yet know what we are doing, yet on the other hand this not knowing is an especially constructive form of not knowing that will help us get a proper perspective on what we are doing and where we should go from here.…”
Section: A New "New Vocabulary": Exploring Cognition Neurosciencesmentioning
confidence: 99%